Implementasi Electronic Record Information System for Education (ERISE) untuk Mengelola Arsip di PT Naturindo Surya Niaga - Qotimah, Qusnul; Yuliansah, Yuliansah (Perpustakaan dan Arsip Universitas Gadjah Mada, 2025)
This study aims to: 1) identify the implementation of the Electronic Record Information System for Education (ERISE) at PT Naturindo Surya Niaga, and 2) identify the challenges faced in the implementation of ERISE at PT Naturindo Surya Niaga. The research uses a descriptive qualitative approach. The subjects in this study are company leaders, archive oﬃcers, and company employees. Data collection methods include observation, interviews, and documentation. Data analysis techniques involve data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of ERISE for archive management at PT Naturindo Surya Niaga includes the following activities: 1) creation and storage, which involves media conversion using a scanning machine, inputting incoming and outgoing letters, and storing these letters in the database; 2) distribution and use, which includes the distribution process using the letter disposition feature, locating archives in the database, and downloading incoming and outgoing letters; 3) maintenance, which involves backup activities, archive security, and scheduling electronic archive maintenance; and 4) disposition, which includes scheduling archive retention and determining ﬁnal actions for archives. The challenges faced during the ERISE implementation process at PT Naturindo Surya Niaga are grouped into three categories: 1) technical challenges related to the ERISE application, 2) human resource (HR) challenges, and 3) challenges related to security and accessibility.